Mathematical Model of Armed Criminal Group with Pre-emitive and Repressive Intervention - Wahyudin Nur; Darmawati Darmawati (Program Studi Matematika Universitas Sulawesi Barat, 2020)
Armed Criminal group is one of the problems faced by many countries in the world. Awful behaviour of armed criminal group members can affect a large amount of people. In this paper, we construct a deterministic mathematical model that takes into account persuasive and repressive intervention. We consider crime as a social epidemic. We determine the armed criminal group free equilibrium point and the armed criminal group persistence equilibrium point together with their existence condition. The next generation matrix is used to obtain the basic reproduction number. The local stability conditions of equilibrium points are proved using linearization. We show that the armed criminal group free equilibrium point is globally asymptotically stable under certain condition. Numerical simulations are performed to support our deductive study.